2015
DOI: 10.1021/jp512404a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Composition on the Nonlinear Optical Response of AuxAg1–x Nano-Alloys

Abstract: The synthesis of variable composition Au x Ag (1−x) alloyed nanoparticles prepared by laser ablation in water is reported. The nanoalloys exhibited a single characteristic surface plasmon resonance peak, whose spectral position was lying between the surface plasmon resonance peaks of neat Ag and Au nanoparticles, at about 400 and 530 nm respectively, depending directly on the composition of the alloyed nanoparticles. The nonlinear optical response of the nanoalloys was studied in details under 532 nm (visible)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 95 publications
(181 reference statements)
2
33
0
Order By: Relevance
“…This suggests that Ag 1 Au 3 alloy enhanced the OL performance of 2 more than Ag 3 Au 1 as earlier observed in the reported β eff . This observation is also in good agreement with NLO studies carried out on Au x Ag 1 −x nano-Alloys at 532 nm, using 35 ps and 4 ns laser pulses, by Papagiannouli and coworkers [7]. They observed that the alloy with the highest Au content had the strongest limiting properties which were attributed to the proximity of plasmon peak of the alloys to the excitation laser source.…”
Section: Eds Spectrasupporting
confidence: 90%
See 4 more Smart Citations
“…This suggests that Ag 1 Au 3 alloy enhanced the OL performance of 2 more than Ag 3 Au 1 as earlier observed in the reported β eff . This observation is also in good agreement with NLO studies carried out on Au x Ag 1 −x nano-Alloys at 532 nm, using 35 ps and 4 ns laser pulses, by Papagiannouli and coworkers [7]. They observed that the alloy with the highest Au content had the strongest limiting properties which were attributed to the proximity of plasmon peak of the alloys to the excitation laser source.…”
Section: Eds Spectrasupporting
confidence: 90%
“…The intense SPR peaks of Ag 3 Au 1 and Ag 1 Au 3 were observed at 423 nm and 482 nm, respectively, Table 1. The SPR peaks of the alloys are very close to the SPR positions of pure AgNPs and AuNPs, depending on the composition of Ag or Au present in the alloys [7].…”
Section: Uv-vis Electronic Spectramentioning
confidence: 75%
See 3 more Smart Citations